Analysis of Criminal Acts Without Rights or Against the Law to Commit Conspiracy in Buying, Receiving, Being an Intermediary in the Sale and Purchase of Narcotics in Decision No. 315/Pid.Sus / 2025 / PN Sbw - Sahputra, Rilawadi (International Asia Of Law and Money Laundering (IAML), 2026)
This study analyzes the application of elements of criminal acts without rights or against the law in conspiracy to buy, receive, and become an intermediary for the sale and purchase of narcotics based on Decision number 315/Pid.Sus / 2025 / PN Sbw. The research method uses normative juridical approach with statute approach and case approach analysis technique to court decision. The results showed that the panel of judges proved all elements of Article 114 paragraph (2) jo. Article 132 paragraph (1) of Law No. 35 of 2009 concerning narcotics systematically, includes elements of "every person", "conspiracy", "without rights or against the law", and "being an intermediary in the sale and purchase of narcotics class I non-plant weighing more than 5 grams". Evidence of conspiracy was made through a structured agreement between Ken, defendant I as a broker, and defendant II as a courier in distributing 36.47 grams of methamphetamine. The panel of judges applied the principle of lex favor reo by implementing Law Number 1 of 2026 concerning criminal adjustments that remove special minimum crimes, thus imposing a prison sentence of 7 years for Defendant I and 5 years for Defendant II without a fine. The conclusion of the study confirms that the proof of conspiracy does not require the implementation of a criminal act perfectly, but enough with the agreement and preparation that leads to the implementation of narcotics crimes.